Development of Haemophilia Treatment in the Eastern Part of Germany over the Last Decade in the Kompetenznetz Hämorrhagische Diathese Ost (KHDO) - Mahn, Rebecca; Schilling, Kristina; Klamroth, Robert; Kentouche, Karim; Aumann, Volker; Fischer, Lars; Holzhauer, Susanne; Sirb, Harry; Scholz, Ute; Trautmann, Karolin; Halm-Heinrich, Ines; Krammer-Steiner, Beate; Koscielny, Jürgen; Kreibich, Ute; Pietrzak-Büttner, Antje; Tregel, Matthias; Knöfler, Ralf; Pfrepper, Christian; and the Kompetenznetzwerk Hämorrhagische Diathese Ost (Hämostaseologie, 2020)
Introduction In 2005 the Kompetenznetz Hämorrhagische Diathese Ost published epidemiologic data about patients with haemophilia A (HA) and haemophilia B (HB) in the eastern part of Germany. This study provides data about the development of treatment in these patients over the past 10 years.Methods Data from 12 haemophilia centres in eastern Germany were retrospectively collected for the year 2015 from patients' records.Results We evaluated 413 patients (115 children, 298 adults) with HA or HB. A total of 286 patients (69.2%) had severe haemophilia (patients with severe haemophilia, PWSH). Compared with 2005, the proportion PWSH on prophylaxis increased from 90% to 98.8% in children and from 64% to 80.2% in adults. The use of plasma-derived factor concentrates decreased from >70% to 55.3% in children and to 55.1% in adults. Mean annual factor consumption in PWSH without inhibitor was higher in 2015 compared with 2005 (children with HA: 151,489 vs. 98,894; adults with HA: 217,151 vs. 151,394; children with HB: 105,200 vs. 64,256; adults with HB: 159,185 vs. 85,295). Median annualized bleeding (annualized bleeding rate, ABR) and joint bleeding rates (annualized joint bleeding rate, AJBR) in 2015 were 2 and 0 in children and 3 and 0 in adults, respectively. In 2015 only one child (1.2%) but 101 (53.2%) adults with severe haemophilia were anti-hepatitis C virus (anti-HCV) positive. The rate of anti-HCV positive patients with active hepatitis C dropped from 63.8% to 12.9%.Conclusions Within the last decade more patients with severe haemophilia were switched to a prophylactic regimen going along with a moderate increase in factor consumption achieving a low ABR and AJBR.
Keywords: haemophilia; epidemiologic data; factor consumption; hepatitis C